Experience With Early Sorafenib Treatment With mTOR Inhibitors in Hepatocellular Carcinoma Recurring After Liver Transplantation. Issue 3 (March 2020) - Invernizzi, Federica; Iavarone, Massimo; Zavaglia, Claudio; Mazza, Stefano; Maggi, Umberto; Cesarini, Lucia; Antonelli, Barbara; Airoldi, Aldo; Manini, Matteo Angelo; Sangiovanni, Angelo; Rossi, Giorgio; Donato, Maria Francesca; et al.
Abstract : Background: Sorafenib (SOR) is currently used for hepatocellular carcinoma (HCC) recurring after liver transplantation (LT) when HCC is unsuitable for surgical/locoregional treatments. We evaluated safety and effectiveness of early introduction of SOR after HCC-recurrence. Methods: All patients with HCC-recurrence after LT treated with SOR in 2 centers were included (January 2008 to June 2018). Baseline and on-treatment data were collected. Results: Fifty patients early treated with SOR for HCC-recurrence after LT (74% mammalian target of rapamycin inhibitor [mTORi], 54% HCC-treated at baseline) were enrolled. During 7.3 (0.3–88) months of SOR, all patients had at least one adverse event (AE), 56% graded 3–4. SOR was reduced in 68%, being AEs the main cause of reduction, and discontinued in 84% (60% symptomatic progression, 33% AE). Objective response was obtained in 16% and stable disease in 50%. Median time to radiological progression was 6 months (95% confidence Interval [CI], 4-8). Thirty-three patients (69%) died, 94% for HCC progression. Median overall survival (OS) was 18 months (95% CI, 8-27); 5-year OS was 18% (95% CI, 4%-32%). Baseline predictors of OS were SOR+mTORi (hazard ratio [HR], 0.4; 95% CI, 0.2-0.9; P = 0.04), previous curative treatments (HR, 0.3; 95% CI, 0.2-0.7; P = 0.003) and alpha-fetoprotein > 100 ng/mL (HR, 2.5; 95% CI, 1.1-5.0, P = 0.02). At multivariate analysis, HCC curative treatment was the only independent predictor (HR, 0.4; 95% CI 0.2-1.0; P = 0.04). Conclusions: Early and combined treatment with SOR and mTORi resulted in a favorable safety profile, while its effectiveness should be confirmed by meta-analysis of previous studies or by larger studies. Curative treatment for HCC resulted the only independent predictor of OS.